Assessment of Two Environmental Indicators in Agave sisalana Seedling Production - Ana Nadja Lopes Lucas; Lorena Rodrigues Cunha; Matheus Martins Teixeira Cota; Edna dos Santos Almeida (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Sisal (Agave sisalana) is a renewable and versatile natural fiber widely used in ropes, rugs, bags, and composite materials for the automotive and construction industries. Beyond its industrial applications, sisal plays an important socioeconomic role, particularly in semi-arid regions such as northeastern Brazil, where it represents a major source of income for local communities. Maintaining this production chain, however, relies on continuous crop renewal, which depends directly on the availability of healthy and sustainable seedlings. In this context, nursery practices become essential for ensuring productivity and controlling phytosanitary problems, such as red rot, which has significantly affected sisal fields since the 1970s. This study evaluates key environmental indicators associated with the production of Agave sisalana seedlings, focusing on Global Warming Potential (GWP) and Cumulative Energy Demand (CED) of fossil origins. A gate-to-gate life cycle assessment was conducted to quantify the contributions of inputs such as fertilizers, polyethylene, electricity, and transportation. Fertilizer use was identified as the largest contributor to GWP (61.8%), while electricity (56.5%) and polyethylene (27.20%) were the largest contributors to cumulative energy demand. These results highlight significant opportunities for sustainability improvements through renewable energy adoption, input optimization, and enhanced operational efficiency. The integrated assessment provides a basis for advancing sustainable nursery practices and reducing the environmental footprint of Agave sisalana seedling production. Nevertheless, a more comprehensive assessment including additional environmental indicators is required to capture the full range of impacts and to guide more robust sustainability strategies.